Chaotic behavior of human thermal plumes in an aircraft cabin mockup. (April 2018) - Wang, Congcong; Liu, Junjie; Li, Jiayu; Li, Fei
Highlights: Unsteady and chaotic behavior of human thermal plumes were showed. Gaussian mixture models were used to evaluate oscillating thermal plume airflow. Evolution of phase space reconstruction of thermal plume airflow was determined. The human thermal plume was demonstrated chaotic airflow quantitatively. Abstract: The human thermal plume induced by body heat loss has a significantly impact on human thermal comfort, contaminant transport and indoor air quality. Few studies focused on the temporal unsteady characteristics of human thermal plume. In this study, the human thermal plume generated by a heated manikin was measured in a 7-row cabin mockup by mini particle image velocimetry (mini-PIV) system; and its unsteady and chaotic behavior was determined out of statistical and chaotic method. Probability density distributions of velocity time series of human thermal plumes presented Gaussian mixture models with two peaks, which substantiated the oscillating characteristics of human thermal plumes. The energy region of the human thermal plume was concentrated between 0.1 Hz and 10 Hz determined out of the power spectrum analysis, and the power spectrum exponent of the human thermal plume above the head ranged from 0.9 to 1.2. Evolution of phase space reconstruction of velocity time series from single-spindle to double-spindle revealed the human thermal plume presents obvious autocorrelation and oscillating behavior qualitatively. In addition, the fractal dimension of human thermal plumes overhead ranged from 6 and 12 without integers and Kolmogorov entropies of analyzed points were all larger than zero indicating the human thermal plume was kind chaotic airflow quantitatively.